Tax Dispute PT. Bank CIMB Niaga, Tbk. in the Tax Court - Analysis of Decision Number: PUT-117384.15/2014/PP/M.XVI.A Year 2020 - Ridho Ribbon Hutapea; Rumainur Rumainur (Budapest International Research and Critics University, 2022)
The Tax Court is a specialty in the judicial system in Indonesia. The technical development of the judiciary for the Tax Courts is carried out by the Supreme Court and the organizational, administrative, and financial development of the Tax Courts is carried out by the Ministry of Finance. The organizational, administrative and financial guidance carried out by the Ministry of Finance has opened up opportunities for conflict not only at the normative level but also raised doubts and polemics for taxpayers. The method used in this study is a qualitative analysis method. Data collection techniques were carried out by document studies, interviews, and observations. Based on the results of the study, it can be concluded that the urgency in tax dispute decisions with ordinary procedures at the first and last levels of PT. Bank CIMB Niaga, Tbk., in Decision Number: PUT.117384.15/2014/PP/M.XV.A of 2020, that the Judges of the Tax Courts decide cases based on their beliefs which do not mean the judge's feelings as humans but the judge's belief that is supported by valid evidence, and regulated in Article 3 Chapter II of Law Number 48 of 2009 concerning Judicial Power, it is explained about the Principles of the Implementation of Judicial Power.